2018
DOI: 10.3329/sja.v15i2.35159
|View full text |Cite
|
Sign up to set email alerts
|

Integrated use of manure and fertilizers increases rice yield, nutrient uptake and soil fertility in the boro-fallow-t.aman rice cropping pattern

Abstract: The effect of integrated use of manure and fertilizers on crop yield, nutrient uptake and soil fertility was studied in the Boro-fallow-T. Aman cropping pattern over two years. The experiment was set up at Bangladesh Agricultural University (BAU) farm, Mymensingh under the AEZ 9 (Old Brahmaputra Floodplain). The field trial consisted of eight treatments and control (no fertilizer or manure), 100% chemical fertilizers (CF), and IPNS based six treatments with six types of manure. Cowdung (CD), CD slurry, Trichoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…In an another study where integrated use of manure with fertilizers gave on an average 8.3-33.8% and 2.9-18.3% higher grain yield in Boro and T. Aman rice, respectively over sole fertilizers treatments (Bilkis et al, 2017).…”
Section: Straw Yield (T/ha)mentioning
confidence: 93%
“…In an another study where integrated use of manure with fertilizers gave on an average 8.3-33.8% and 2.9-18.3% higher grain yield in Boro and T. Aman rice, respectively over sole fertilizers treatments (Bilkis et al, 2017).…”
Section: Straw Yield (T/ha)mentioning
confidence: 93%
“…Roobroeck et al [16] reported that ISFM can significantly enhance the crop productivity and profitability of farmers. Bilkis et al [17] reported that integrated application of Trichocompost and cow dung bio-slurry in rice field increases rice yield, where Trichocompost was found to be more effective than the bio-slurry. The better performance of LC may be due to higher nutrient contents, including Zn, enlarging soil volume for nutrient and water uptake by fungal hyphae, reducing pest infestation [18], and functioning as a plant growth promoter [47].…”
Section: Effect Of Management Practices On the System Productivitymentioning
confidence: 99%
“…The ISFM has attracted the interest of scientists worldwide with its benefits for increased crop yield and sustainable soil health [16]. Recently, Trichocompost, produced from Trichoderma sp., has been reported to improve crop yield by increasing availability of plant nutrients and water to plants through their enlarged hyphae and by preventing pest infestation [17,18]. Understanding how a proactive choice of organic amendment, as in the case of ISFM in MT systems, can help reduce the requirements for N application.…”
Section: Introductionmentioning
confidence: 99%
“…The use of inorganic fertilizers in conjunction with organic resources resulted in the highest grain and straw yields [1]. Using organic manure and chemical fertilizers in tandem would be very promising, not just in terms of increasing output stability but also in terms of improving soil fertility [2].…”
Section: Introductionmentioning
confidence: 99%
“…The use of organic manure in conjunction with chemical fertilizers can significantly boost rice output and soil productivity [12]. In a rice-rice cropping pattern, the integrated use of chemical and organic manure is critical for long-term crop productivity and soil fertility [2]. Soil organic matter boosts crop output by improving the physicochemical characteristics of the soil.…”
Section: Introductionmentioning
confidence: 99%